Iodine Density of Lymphoma, Metastatic SCCA, and Normal Cervical lymph nodes: A Comparative Analysis Based on DLSCT [version 2; peer review: 2 approved] - Urusaya Wangprasertkul; Arvemas Watcharakorn; Warit Tarathipmon; Varalee Mingkwansook (F1000Research)
Objective To compare iodine density (ID) and contrast-enhanced attenuation value (CEAV) from dual-layer spectral computed tomography (DLSCT) scans of lymphomatous, metastatic squamous cell carcinoma (SCCA), and normal cervical lymph nodes. Methods Data including ID and CEAV were retrospectively collected from patients who underwent DLSCT of the neck between January 2020 and August 2023. Results from each group (lymphomatous, metastatic SCCA, and normal) were compared and analyzed using one-way ANOVA and receiver operating characteristic curve. Results 129 cervical lymph nodes were collected from patients who met the inclusion criteria (50, 41, and 38 nodes from the lymphomatous, metastatic SCCA, and normal group, respectively). The mean ID of lymphomatous, metastatic SCCA, and normal nodes was 1.01±0.27, 1.36±0.28, and 1.45±0.29 mg/mL, respectively. Comparing lymphomatous nodes with metastatic SCCA nodes, the lymphomatous nodes had significantly lower values of ID (p<0.002) and CEAV (p<0.001). Similarly, when comparing lymphomatous nodes with normal nodes, the lymphomatous nodes had significantly lower values of ID (p<0.001) and CEAV (p<0.001). The optimal ID cut-off value for distinguishing between lymphomatous and metastatic SCCA nodes was 1.175 mg/ml (specificity of 84.2%, sensitivity 77.8%, AUC 0.788, P = 0.003). The optimal CEAV cut-off value was 77.5 HU (specificity 88.9%, sensitivity 78.9%, AUC 0.851, P<0.001). Conclusions The ID and CEAV measurements from DLSCT were significantly different between lymphomatous, metastatic SCCA, and normal lymph nodes. These findings indicate that DLSCT can be used to distinguish between these conditions in the diagnosis of cervical lymph nodes.